Deskripsi Tempat Penampungan Air Positif Larva Aedes aegypti di Kelurahan Cakung Timur - Aulia, Sitti; Djamahar, Refirman; Rahmayanti, Rahmayanti (LPPM Universitas Negeri Jakarta, 2014)
Abstract The purpose of this study is describing the larva of Aedes aegypti positive water reservoir in Cakung Timur District, which is one of the endemic DHF areas. This is a descriptive research. This research was conducted to 100 residential houses, on October 2010. Larva that gets from water reservoir was brought to FMIPA UNJ laboratory to be examined further. There were 606 water reservoirs found in Cakung Timur District and 5.61% were Aedes aegypti larva positive. Type of water reservoir in Cakung Timur District with a potentially large against Aedes aegypti transmission is bath (15.13%), crock (4.80%), buckets (1.35%), and well (14.29%). Key words: Aedes aegypti larva, Cakung Timur District, water reservoir